Analysis Policy Overtime And Culture Organization To Employee Performance Bank Syariah Indonesia (BSI) PALOPO Branch Office - Muh. Hidayat Yasruddin; Saharuddin; Sari Ratna Dewi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
writing of this research article entitled "Analysis of Overtime Policy and Organizational Culture on Employee Performance of Bank Syariah Indonesia (BSI) KC Palopo". This study investigates how organizational culture and overtime policy affect employee performance at Bank Syariah Indonesia (BSI) KC Palopo. This study uses multiple linear regression analysis using the SPSS program and involves 40 respondents. In the t-test, the t-value for the overtime policy is 5.019, which is greater than the t table of 2.026. In addition, the significance value for the overtime policy variable is 0.000. The results of the study indicate that the overtime policy affects employee performance positively and significantly, and the t-value for the organizational culture variable of 3.062 is greater than the t table, and the significance value for the organizational culture variable is 0.004, which is smaller than 0.05. The results of the study indicate that organizational culture affects employee performance positively and significantly.